Prandtl Number Effects on Mixed Convection Between Rotating Coaxial Disks - Chyi-Yeou Soong (International Journal of Rotating Machinery, 1996)
Prandtl number characterizes the competition of viscous and thermal diffusion effects and, therefore, is an influential factor in thermal-fluid flows. In the present study, the Prandtl number effects on non-isothermal flow and heat transfer between two infinite coaxial disks are studied by using a similarity model for rotation-induced mixed convection. To account for the buoyancy effects, density variation in Coriolis and centrifugal force terms are considered by invoking Boussinesq approximation and a linear density-temperature relation. Co-rotating disks (Ω2=Ω1) and rotor-stator system (Ω1≠Ω2=0) are considered to investigate the free and mixed convection flows, respectively. For Reynolds number, Re, up to 1000 and the buoyancy parameter, B=βΔT, of the range of |B|≤0.05, the flow and heat transfer characteristics with Prandtl numbers of 100, 7, 0.7, 0.1, and 0.01 are examined. The results reveal that the Prandtl number shows significant impact on the fluid flow and heat transfer performance. In the typical cases of mixed convection in a rotor-stator system with |B|=0.05, the effects in buoyancy-opposed flows B=0.05 are more pronounced than that in buoyancy-assisted ones.